Potential Benefit of Melatonin as an Adjuvant Therapy in a Sample of Iraqi Patients with Crohn’s Disease: A New Study - Saleh, Hussein Hazim; Abdulridha, Manal Khalid; Najeb, Akram Ajeel (Al Mustansiriyah Journal of Pharmaceutical Sciences, 2018)
Inflammatory bowel disease (IBD) is considered as a general term for groups of idiopathic, chronic, relapsing inflammatory disorders of the GIT. Inflammatory bowel disease (IBD) can be divided into two main diseases: Ulcerative colitis (UC) and Crohn’s disease (CD). Melatonin (N-acetyl-5-methoxytryptamine) is a hormone that is secreted from a pineal gland and other tissues such as gastrointestinal tract (GIT). This study was intended to evaluate the potential effectiveness of melatonin as an adjuvant to the standard treatment. This interventional prospective randomized-controlled, open-label, single center study was carried out on 30 patients visiting the Biological Unit/Baghdad Teaching Hospital/Medical City Directorate, for their scheduled standard treatment for moderate to severe CD during the period from August 2016 to March 2017. Ethical committee approval and patients written consent were obtained. Hemoglobin (Hb) level in CD patients was significantly increased after both regimen (standard treatment and melatonin adjuvant therapy), but no significant difference in hemoglobin between the two groups. The erythrocyte sedimentation rate (ESR) level was significantly decreased after both regimens (P<0.05) with no significant difference was found between patients groups. The tumor necrosis factor (TNF-α) level was not affected after both regimens in CD patients. From the present study, a promising therapeutic strategy emerged in respect to melatonin as adjuvant therapy in patients with CD which may suggest a role in ameliorating disease process both subjectively and objectively thus optimize therapeutic outcome